Uzdrowienie w szabat człowieka chorego na puchlinę wodną jako creatio continua (Łk 14,1-6) - Nowak, Dominik (Śląskie Studia Historyczno-Teologiczne, 2011)
In his mission of proclaiming Gods kingdom, Jesus was driven first of all by his compasion for other human beings. His misssion was reaveled through his words and deeds, and it was a testimony of Gods love for humans. The creative perspective of the Saviours work is reavealed particularly by appealing to the idea of love. In modern biblical theology, the image of Gods love became the hermeneutical key for explaining the mystery of creation. Since it is difficult to state clearly what the creation ex nihilo – something out of nothing is, more and more often it is talked about as creation ex amore – out of love. Jesus was undertaking the work of creation in his activities. In this way he became the Creator full of love for all his cration, especially for the one which – paraphrasing the words of apostle Paul – „one sighs and hurts, awaiting ones redemtion” (Rome 8,22). Healings performed by Jesus, especialy the ones performed on the sabath, are written in the notion of creatio continua. His healing work on the sabath can be described as creatio contunua ex amore.